2014
DOI: 10.1097/acm.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Learning About Medical Student Mistreatment From Responses to the Medical School Graduation Questionnaire

Abstract: Although evidence of medical student mistreatment has accumulated for more than 20 years, only recently have professional organizations like the Association of American Medical Colleges (AAMC) and the American Medical Association truly acknowledged it as an issue. Since 1991, the AAMC's annual Medical School Graduation Questionnaire (GQ) has included questions about mistreatment. Responses to the GQ have become the major source of evidence of the prevalence and types of mistreatment. This article reviews natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
126
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 11 publications
3
126
1
4
Order By: Relevance
“…Mistreatment can have deleterious effects on medical students’ emotional well-being and professional attitudes [1,2]. Specifically, medical students who are subject to abusive behaviors are more likely to experience mental health issues such as post-traumatic stress [3,4], depression and low career satisfaction [5], and even suicidality [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mistreatment can have deleterious effects on medical students’ emotional well-being and professional attitudes [1,2]. Specifically, medical students who are subject to abusive behaviors are more likely to experience mental health issues such as post-traumatic stress [3,4], depression and low career satisfaction [5], and even suicidality [6].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, medical students who are subject to abusive behaviors are more likely to experience mental health issues such as post-traumatic stress [3,4], depression and low career satisfaction [5], and even suicidality [6]. More than three decades of studies have shown that the behavior of faculty, residents, and nurses toward medical students can be unprofessional and abusive, particularly during clinical clerkship rotations [1,5,7,8]. A meta-analysis demonstrated a high prevalence of harassment and discrimination toward medical trainees worldwide, with 59% of medical trainees experiencing at least one form of harassment or discrimination during their training [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, 13 to 20 percent of graduating medical students report that they have been mistreated, with clinical settings the mostly likely place for these incidents [4]. When medical schools are compared, the proportion of graduates reporting mistreatment varies widely from approximately 5 to 40 percent, but averaging 17 percent [5]. subjective experience in determining whether or not mistreatment has occurred.…”
mentioning
confidence: 99%
“…2 More troubling, national surveys of US medical graduates between 2000 and 2011 found that 25% reported mistreatment that included sexist names or remarks and that 13% had experienced unwanted sexual advances, some involving medical colleagues or supervisors. 3 There exists a wider societal problem of gender-based violence and victimization. Statistics Canada documented 21 300 reported assaults in Canada in 2013.…”
mentioning
confidence: 99%